2012
DOI: 10.1155/2012/269756
|View full text |Cite
|
Sign up to set email alerts
|

Coinhibitory Molecules in Autoimmune Diseases

Abstract: Coinhibitory molecules such as CTLA-4, PD-1 and BTLA negatively regulate immune responses. Multiple studies indicate that the deficiency or mutation of coinhibitory molecules leads to the development of autoimmune diseases in mice and humans, indicating that the negative signals from coinhibitory molecules are crucial for the prevention of autoimmunity. In some conditions, the administration of decoy coinhibitory receptors (e.g., CTLA-4 Ig) or mAb against coinhibitory molecules suppresses the responses of self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…Abatacept, a fusion protein composed of the Fc fragment of human IgG1 linked to the extracellular domain of CTLA-4, has shown efficacy in a broad spectrum of RA patients from early stage to refractory diseases that are resistant to TNF blockers (8184). …”
Section: Cd8+ Ts Cells In Autoimmune Diseasesmentioning
confidence: 99%
“…Abatacept, a fusion protein composed of the Fc fragment of human IgG1 linked to the extracellular domain of CTLA-4, has shown efficacy in a broad spectrum of RA patients from early stage to refractory diseases that are resistant to TNF blockers (8184). …”
Section: Cd8+ Ts Cells In Autoimmune Diseasesmentioning
confidence: 99%
“…As with CTLA-4 (cytotoxic T-lymphocyte-associated protein 4) and BTLA (B-and T-lymphocyte attenuator), a major function of PD-1 is to prevent the activated T cells from becoming overzealous, leading to adverse inflammatory responses and organ damage (22)(23)(24). PD-1 is a membrane protein of the CD28 family.…”
mentioning
confidence: 99%
“…PD-1 is a membrane protein of the CD28 family. It is expressed on the surfaces of many immune cells, including CD4 ϩ T cells, CD8 ϩ T cells, NK T cells, B cells, and monocytes (22,24,25). Its ligand PD-L1 (CD274), also called B7 homolog 1 (B7-H1), is a type I transmembrane protein and is constitutively expressed on T cells, B cells, macrophages, and dendritic cells (22,24,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphisms in CTLA-4 have been linked to diabetes mellitus, Hashimoto's thyroiditis, celiac disease, and primary biliary cirrhosis (13). It has been suggested that in the presence of these polymorphisms the inhibitory effect of CTLA-4 is impaired (12).…”
mentioning
confidence: 99%